Immobilization and property of penicillin G acylase on amino functionalized magnetic Ni0.3Mg0.4Zn0.3Fe2O4 nanoparticles prepared via the rapid combustion process - Ma, Mingyi; Chen, Xiu; Yue, Yao; Wang, Jie; He, Dawei; Liu, Ruijiang (Frontiers in Bioengineering and Biotechnology, 2023)
Penicillin G acylase plays an important role in the biocatalytic process of semi-synthetic penicillin. In order to overcome the disadvantages of free enzymes and improve the catalytic performance of enzymes, it is a new method to immobilize enzymes on carrier materials. And magnetic materials have the characteristics of easy separation. In the present study, the Magnetic Ni0.3Mg0.4Zn0.3Fe2O4 nanoparticles were successfully prepared by a rapid-combustion method and calcined at 400°C for 2 h. The surface of the nanoparticles was modified with sodium silicate hydrate, and the PGA was covalently bound to the carrier particles through the cross-linking of glutaraldehyde. The results showed that the activity of immobilized PGA reached 7121.00 U/g. The optimum pH for immobilized PGA was 8 and the optimum temperature was 45°C, the immobilized PGA exhibited higher stability against changes in pH and temperature. The Michaelis–Menten constant (Km) values of the free and immobilized PGA were 0.00387 and 0.0101 mol/L and the maximum rate (Vmax) values were 0.387 and 0.129 μmol/min. Besides, the immobilized PGA revealed excellent cycling performance. The immobilization strategy presented PGA had the advantages of reuse, good stability, cost saving and had considerable practical significance for the commercial application of PGA.